Three Inuit men (Paul Luck, father and son) on board whaling schooner Era, Cape Fullerton, Hudson Bay, Canada - Comer, George (Creator) (Ownership Statement: Mystic Seaport, 1901)
Three Inuit men, pose inside the deckhouse on board the whaling schooner Era, Cape Fullerton, Hudson Bay, Canada, May 17, 1901. Infrastructure Lifestyle Title supplied by cataloger. Information from original envelope identifies this as Photo #33A, # 75. George Comer identified the men as Paul Luck (or Luke), with father and son The schooner Era was built in 1847 at Boston, Massachusetts. She was a New London whaling vessel until her last voyage out of that port in 1892; her masters included James Monroe Buddington, John O. Spicer, and George Comer. She was wrecked off Miquelon Island, July 27, 1906. Taken by Captain George Comer (1858-1937), a sealer and whaling captain from East Haddam. He went to sea while still in his teens and was later master of vessels from both New London and New Bedford. Comer participated in voyages involved in polar expeditions and was noted for his studies of Arctic peoples and their environment.